The coupling curve between urbanization and the eco-environment: China’s urban agglomeration as a case study - Chuanglin Fang (Elsevier, 2021)
Urbanization is one of the most consequential human activities on earth. The contradictions between urbanization and the eco-environment are particularly prominent in urban agglomerations with high industrial concentrations. Based on the Environmental Kuznets Curve (EKC) theory, we propose the hypothesis of the Urbanization-EKC (UEKC), which states that in the process of urbanization, eco-environmental quality first deteriorates and then improves, following a “U” trend. Taking 19 Chinese urban agglomerations as empirical cases, this paper analyzed the multi-dimensional coupling curves between urbanization and the eco-environment. The results show that the coupling curves between urbanization and the eco-environment are heterogeneous, as a result of differences among urban agglomerations and various eco-environmental indicators. In five mega-urban agglomerations, we found that the coupled curve of urbanization and eco-environmental quality index (EQI) is a compound function containing logarithm and quadratic terms, following the “U” curve shape of “quick down, slow up”; the turning point of EQI improvement was found at an urbanization rate of 47%. The empirical results validate that the UEKC hypothesis is tenable for developed urban agglomerations. This study provides a methodological reference for researching the evolutionary relationship between urbanization and the eco-environment and provides decision support for a more harmonious development of humans and nature in China's urban agglomerations.